Investigating the Effect of Selected Non-Saccharomyces Species on Wine Ecosystem Function and Major Volatiles - Bagheri, Bahareh; Zambelli, Paolo; Vigentini, Ileana; Bauer, Florian Franz; Setati, Mathabatha Evodia (Frontiers in Bioengineering and Biotechnology, 2018)
Natural alcoholic fermentation is initiated by a diverse population of several non-Saccharomyces yeast species. However, most of the species progressively die off, leaving only a few strongly fermentative species, mainly Saccharomyces cerevisiae. The relative performance of each yeast species is dependent on its fermentation capacity, initial cell density, ecological interactions as well as tolerance to environmental factors. However, the fundamental rules underlying the working of the wine ecosystem are not fully understood. Here we use variation in cell density as a tool to evaluate the impact of individual non-Saccharomyces wine yeast species on fermentation kinetics and population dynamics of a multi-species yeast consortium in synthetic grape juice fermentation. Furthermore, the impact of individual species on aromatic properties of wine was investigated, using Gas Chromatography-Flame Ionization Detector. Fermentation kinetics was affected by the inoculation treatment. The results show that some non-Saccharomyces species support or inhibit the growth of other non-Saccharomyces species in the multi-species consortium. Overall, the fermentation inoculated with a high cell density of Starmerella bacillaris displayed the fastest fermentation kinetics while fermentation inoculated with Hanseniaspora vineae showed the slowest kinetics. The production of major volatiles was strongly affected by the treatments, and the aromatic signature could in some cases be linked to specific non-Saccharomyces species. In particular, Wickerhamomyces anomalus at high cell density contributed to elevated levels of 2-Phenylethan-1-ol whereas Starm. bacillaris at high cell density resulted in the high production of 2-methylpropanoic acid and 3-Hydroxybutanone. The data revealed possible direct and indirect influences of individual non-Saccharomyces species within a complex consortium, on wine chemical composition.